2014
DOI: 10.1371/journal.pmed.1001729
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Evaluating Progress towards Universal Health Coverage in Tunisia

Abstract: This paper is a country case study for the Universal Health Coverage Collection, organized by WHO. Mohamed Kouni Chahed and colleagues illustrate progress towards UHC and its monitoring and evaluation in Tunisia. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Previous literature on financial inclusion in the KSA has mainly focused on its effects on levels of development and poverty, 21,22 the prevalence of financial exclusion in the presence of growth in the financial sector 23 and the gender differentials. 24 The findings' consensus points to the narrative that individuals with deprived backgrounds and the poor are more likely to face financial hardships and the results from the Gulf region are in tandem with estimates from Tunisia, 25 Lebanon, 26 the GCC, 27 and in other European regions. 28 There is a dearth of empirical findings from the GCC countries, including the KSA, concerning financial inclusion and financial hardships in public health.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous literature on financial inclusion in the KSA has mainly focused on its effects on levels of development and poverty, 21,22 the prevalence of financial exclusion in the presence of growth in the financial sector 23 and the gender differentials. 24 The findings' consensus points to the narrative that individuals with deprived backgrounds and the poor are more likely to face financial hardships and the results from the Gulf region are in tandem with estimates from Tunisia, 25 Lebanon, 26 the GCC, 27 and in other European regions. 28 There is a dearth of empirical findings from the GCC countries, including the KSA, concerning financial inclusion and financial hardships in public health.…”
Section: Introductionmentioning
confidence: 92%
“…There is a dearth of empirical findings from the GCC countries, including the KSA, concerning financial inclusion and financial hardships in public health. 25 , 27 It is not known how financial inclusion might enhance borrowing for medical purposes and access to emergency funds. Financial inclusion through UHC can lead to improved population health and, therefore, accessing necessary healthcare without financial hardship is one of the key components of UHC.…”
Section: Introductionmentioning
confidence: 99%
“…Country case studies and technical reviews were conducted as part of the development of a global monitoring framework by World Health Organization (WHO) and the World Bank Group. The country case studies [5] [17] aimed to document what indicators, measurement, and communication approaches work best to monitor progress towards UHC. The technical review papers addressed issues related to the measurement of financial protection [18] , service coverage [19] , effective coverage [20] , equity and UHC [21] , and as an example of a health program, the implications for tuberculosis program monitoring [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent data showed that the Tunisian household spend a lot of money on healthcare, and the average out of pocket payments represented almost 45% of the total health expenditure in 2010 (Chahed & Arfa, ). Furthermore, although CNAM partially covers birth‐related health expenses at private facilities, it does not cover costs related to premature births, which are much higher.…”
Section: Healthcare Coverage In Tunisiamentioning
confidence: 99%